Post-Pomo Hip-Hop Homos: Hip-Hop Art, Gay Rappers, and Social Change - Wilson, D. Mark (Social justice, 2007)
Part of a special issue on the relationship between art, identity, and social justice. A study was conducted to examine the contributions and political activism of lesbian, gay, bisexual, transsexual, and queer hip-hop artists. Data were obtained from interviews and field work with the gay hip-hop crew Deep Dick Collective (D/DC). Findings revealed that D/DC's call for social action and its willingness to engage with critique and contradiction challenge other progressive movements to reflect critically on the social identities and social realities of people they would rather disregard. Findings also revealed that D/DC's art presents to hip-hop and other progressive movements of change a willingness to admit that these movements have limitations regarding issues of identity, and that these limitations require constant self-critique and self-examination. Findings are discussed in detail.